2020
DOI: 10.3389/fbioe.2020.547857
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the DNA Stability in Aqueous Solutions of Ionic Liquids

Abstract: Deoxyribonucleic acid (DNA) carries the genetic information essential for the growth and functioning of living organisms, playing a significant role in life sciences research. However, the long-term storage and preservation of DNA, while ensuring its bioactivity, are still current challenges to overcome. In this work, aqueous solutions of ionic liquids (ILs) were investigated as potential preservation media for double stranded (dsDNA). A screening of several ILs, by combining the cholinium, tetrabutylammonium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In addition to the choline-based ILs, other cation–anion combinations were also explored as potential stabilizing media for DNA. ,, In a recent publication, Dinis et al examined DNA stability in a series of hydrated IL solutions . Different ILs were prepared by combination of cholinium, tetrabutyl­ammonium, tetrabutyl­phosphonium, and 1-ethyl-3-methyl­imidazolium cations with bromide, chloride, dihydrogen phosphate, acetate, and glycolate anions.…”
Section: Dna Complexation With Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the choline-based ILs, other cation–anion combinations were also explored as potential stabilizing media for DNA. ,, In a recent publication, Dinis et al examined DNA stability in a series of hydrated IL solutions . Different ILs were prepared by combination of cholinium, tetrabutyl­ammonium, tetrabutyl­phosphonium, and 1-ethyl-3-methyl­imidazolium cations with bromide, chloride, dihydrogen phosphate, acetate, and glycolate anions.…”
Section: Dna Complexation With Ionic Liquidsmentioning
confidence: 99%
“…While DNA or RNA in an aqueous buffer solution can be handled with reasonable stability at room temperature, its storage requires refrigeration at −20 °C (short-term storage) or −80 °C (long-term storage). , The low temperature is necessary to prevent nucleic acids from chemical and enzymatic degradation, but at the same time it also limits the application range of nucleic acids as polymeric materials. It has been shown that ionic liquids (ILs) interact with DNA to form complexed structures, leading to the stabilization of DNA for extended periods of time at room temperature. The stabilization mechanism is mainly attributed to electrostatic and hydrophobic interactions, and studies exploring the stability of DNA in various ILs have been reported. ,, Moreover, the utilization of DNA–IL complex has also led to new material development including ion conductive films and templates for nanoparticle synthesis. …”
Section: Introductionmentioning
confidence: 99%
“…First, despite the generally stable nature of DNA, it may also lose bioactivity in the presence of DNase and some chemicals. [ 107 ] Second, the difficulty in the delivery of DNA into nuclear also dampens the effectiveness of vaccination. Moreover, the proteins produced under the guidance of the DNA in the body may be taken for endogenous substances, which have the possibility to induce immune tolerance rather than immune activation.…”
Section: Platforms For Dna/dna Analogue Deliverymentioning
confidence: 99%
“…DNA is reported to be stable in most cases, but it can also interact with other chemicals as well as be degraded by DNases. [ 107 ] DNA vaccines may be exposed to a complex environment in vivo for a certain period of time before transfection taking place. [ 106b ] Besides, as DNA naturally exists in the human body, pharmacokinetics study of exogenous DNA is important that may affect both the effectiveness and the systemic toxicity.…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…Gene therapeutics are internalized to intracellular vesicles called endosomes, which contain many digestive enzymes that can degrade nucleic acids. Moreover, endosomal pH acidifies progressively as they transition from early to late endosomes and finally to lysosomes, nucleic acids, especially DNA, are not stable at such a low pH [28]. Therefore, gene therapeutics must escape the endosomal pathway in its early stage to avoid being exposed to low pH and catalytic enzymes.…”
Section: Why Does Gene Therapy Need a Carrier?mentioning
confidence: 99%